Space, Power and the Public Library: A Multicase Examination of the Public Library as Organized Space - Griffis, Matthew (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper reports on a doctoral study in progress which examines the spatial organization of three public library buildings. The paper comments on the materially-embedded relations of power between the library and its users, paying special attention to socio-spatial models of control dating from the age of modern library design. Cette communication porte sur une étude doctorale en cours qui examine l’organisation spatiale de trois bibliothèques publiques. L’auteur commente les relations de pouvoir que l’on retrouve entre la bibliothèque et ses usagers, avec une attention particulière aux modèles de contrôle socio-spatiaux issus du design des bibliothèques modernes.